Double or Nothing!? Small Groups Making Decisions Under Risk in ""Quiz Taxi"" - Klemens Keldenich; Marcus Klemm (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This paper investigates the behavior of contestants in the game show Quiz Taxi when faced with the decision whether to bet the winnings they have acquired on a final double or nothing question. The decision is made by groups of two or three persons. This set-up enables the decision making process to be studied by observing group communication. There is a strong correlation between communication content and the final choice, indicating that, from the contestant's perspective, the decisions are rational and that the context is an important factor in the final decision. This is particularly so for individual valuations of the money at stake. More extensive discussions help to make the right decision. As contestants do not apply to go on the show, they represent a less selected sample than those in previous game show studies. Overall, the contestants show risk averse behavior, suggesting CRRA-parameters larger than 1. The study also shows some heterogeneity in attitude to risk. Contestants who do better in the show are more likely to go for the risky option, because they are more knowledgeable and more confi dent. All-female groups are less likely and three-person groups more likely to choose the risky option. – – Diese Studie untersucht das Verhalten der Kandidaten der Fernsehshow Quiz Taxi. Die Kandidaten müssen entscheiden, ob sie eine zuvor erspielte Gewinnsumme für eine finale Doppelt oder Nichts-Frage einsetzen. Da die Kandidaten immer zu zweit oder zu dritt spielen, kann durch Beobachtung der Kommunikation innerhalb der Gruppen der Entscheidungsprozess analysiert werden. Die Kommunikationsinhalte hängen stark mit der finalen Entscheidung zusammen. Dies weist darauf hin, dass die Entscheidungen - aus Sicht der Kandidaten - rational sind und dass der Gesamtzusammenhang, in dem die Entscheidung gesehen wird, wichtig ist. Dies trifft speziell auf die individuellen Bewertungen der auf dem Spiel stehenden Gewinnsumme zu. Da die Teilnehmer sich nicht aktiv für Quiz Taxi bewerben können, stellen sie im Vergleich zu anderen Quizshow-Studien eine weniger selektierte Stichprobe dar. Insgesamt ist das Verhalten der Kandidaten risikoavers, was CRRA-Parameter von mindestens 1 nahelegt. Außerdem zeigen sich Unterschiede in den Risikoeinstellungen verschiedener Gruppen: Kandidaten, die im Verlauf der Show besser abschneiden, entscheiden sich eher für das Risiko, da sie über mehr Wissen und/oder mehr Selbstvertrauen verfügen. Frauengruppen entscheiden sich seltener und 3-Personen-Gruppen häufiger für Doppelt oder Nichts.
Keywords: C93; D70; D81; 330; Risk attitude; game show; communication; group decision; Risk attitude; game show; communication; group decision